Selection Criteria for Oils, Surfactants, and Co-Surfactants in Ocular Nanoemulsion Formulation: A Mini Review - Kishore, Ankita; Jain, Adarsh; Asthana, Navdeep; Milan, Rhytham; Mohanalakshmi, Sabapathi; Gupta, Madhu; Mahor, Alok Kumar; Kanoujia, Jovita (Current Pharmaceutical Design, 2025)
The ocular nanoemulsions (NE) are biphasic systems mainly composed of oil and water emulsified by surfactants/cosurfactants. The extensive surface area of ocular NE enhances corneal contact, leading to improved drug penetration and making it a preferable delivery system. They can also increase the solubility of drugs across the ocular barrier with improved residence time. Oils, surfactants, and co-surfactants used in formulating ocular NEs present a significant challenge in developing safe, stable, less irritant, more permeable, improved residence time, and highly bioavailable products. The choice of oil, surfactant, and co-surfactant significantly impacts the development of ocular Nano emulsions (NE) with desirable characteristics, such as small globule size, enhanced penetration, high drug content, and prolonged retention in the eye. This mini-review aims to contribute valuable insights into the selection criteria of oils, surfactants, and co-surfactants for ocular NE. Finally, the correlation between the properties of ocular NEs and the choice of oils, surfactants, and co-surfactants with emphasis on sterilization and stability aspects are considered in short.
Keywords: co-surfactants